AN ANALYSE CORRELATION OF CONCENTRATION NITRATE, PHOSPHATE AND SILICATE WITH THE ABUNDANCE OF DIATOMS ON NORTH COAST BENGKALIS ISLAND, BANTAN DISTRICT - Gregorius Agung; Irvina Nurrachmi; Yusni Ikhwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted in February 2015 in the North Coast Bengkalis Island, Bantan District. The purpose of this study was to analyze the correlations between the concentration of nitrate, phosphate and silicate as well as an abundance of diatoms, to provide information about fertility waters seen from the content of nitrate, phosphate and silicate as well as an abundance of diatoms in the water, so it can be used as a reference for the development of fisheries and the preservation of ecosystems in a sustainable manner, The research was used purposive sampling method with 3 stations and each station there are four sampling points. The results showed that the concentration of Nitrate, Phosphate and Silicate i.e 0.0747 mg/L; 0.0586 mg/L; 0.0542 mg/L . Diatom species were found 11 species i.e: Rhizosoleniaalata, Rhizosoleniadelicatula, Skeletonemacostatum, Lauderia borealis, NitzschiaSeriata, Isthmia SP, Biddulphiapulchella, Rhizosoleniaindica, Aulacoseria granulate, Lepctocylindrusanmeus and Ceralaulinadentata. An abundance of diatoms at Station 1 , Station 2 and Station 3 as much as 1916.67 Ind/L ; 1316.67 Ind/L ; 3241.67 Ind/L. The results of Regression test showed that nitrate concentrations correlations with diatom abundance of very strong correlation with the value of r (correlation coefficient) = 0.946. Relations with the abundance of diatoms phosphate concentrations are very strong correlations with the value of r (correlation coefficient) = 0.988. Relations with the silicate concentration of diatom abundance of strong correlationss with the value of r (correlation coefficient) = 0,550.Keywords: Nitrate, Phospate, Silicate, Abundance Diatoms,